Effect of pre-treatment with simvastatin in aged rats with abdominal sepsis - Medeiros, Aldo Cunha; Costa, Mariana Coelho; Calife, Emily Ramos; Costa, Marianna Santos Tinoco da; Rêgo, Amália Cínthia Meneses; Medeiros, Vítor Brasil; Araújo-Filho, Irami; Carvalho, Marília Daniela Ferreira (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Background/purpose: Sepsis is a severe inflammatory disease, high-risk, representing the immune response to infection with high morbidity and mortality. It is a particularly serious problem in the geriatric population. Advanced age is a risk factor for worsening of the infection, and the inhibition of inflammation is one of the many pleiotropic effects of statins. The objective of this study was to assess whether pretreatment with simvastatin alters the response of the elderly rat with abdominal sepsis model. Methods: We examined: 1- The effect of simvastatin on survival and the prevention and treatment of abdominal sepsis induced by cecal ligation and puncture (CLP). 2- Effect of simvastatin in the expression of proinflammatory cytokines and quantification of peripheral blood leukocytes. Twenty four Wistar rats were used: 12 young (3 months old). Six rats were treated with simvastatin v.o. and 6 with 0.9% saline solution; Six aged animals (24 months old; n=6) were treated with simvastatin and 6 with 0.9% saline solution. Results: In the aged rats treated with simvastatin 2 deaths occurred. One held 6 hours after CLP and the other one after 16 hours. In the young rats with sepsis treated with saline (n = 6), there was 1 death. In aged animals treated with simvastatin (n = 6) the number of total leukocytes and neutrophils was significantly lower in those treated with saline, the same occurring in young animals (p<0.05). Comparing the old and young animals treated with saline, no significant differences were observed in total leukocyte count (p> 0.05). As for lymphocytes, no significant differences between groups (p> 0.05) were observed. It was found that the % eosinophils was significantly higher in young animals treated with simvastatin compared to aged animals (p <0.05). Overall animals treated with simvastatin showed percentage of eosinophils significantly higher than those treated with saline. Serum levels of TNF?, IL-1? and IL-2 showed significantly higher values in older animals treated with simvastatin than in young rats treated with the same drug (p<0.05). Comparing the old and young saline-treated animals, the values in the measurement of cytokines were consistently higher in the elderly, with no statistically significant differences (p> 0.05). Conclusion: This study demonstrated that in vivo administration of simvastatin, an inhibitor of HMG-CoA reductase inhibitor, decreased mortality, the leukocyte counts in peripheral blood and the expression of proinflammatory cytokines, attenuating abdominal sepsis in aged rats, in which the response to sepsis was more intense than in young animals. These observations may help to extend a new field in the therapeutic use of statins with respect to the attenuation of inflammation in cases of abdominal sepsis in the elderly.